Hubungan antara Iklim Organisasi Kerja dengan Kedisiplinan Karyawan - Muhammad Wardianto (Ilmu Psikologi Universitas Yudharta Pasuruan)
Currently we still meet a lot in a work organization where employee discipline is always demanded but the working climate does not match what is expected by the employee. Or in other words the work climate of the organization is not taken seriously. This research was conducted for knowing the relation between work organization climate and employee discipline. The subjects in this study were structural employees of the University of Yudharta Pasuruan. Collection of information in this study using a discipline scale with a validity coefficient of 0.3 to 0.607 and a reliability efficiency of 0.804; and the scale of work organization climate with a validity coefficient of 0.302 to 0.648 and a reliability efficiency of 0.8608. The results showed that there is a relation between the climate of work organizations with employee discipline, where rxy 0.9385 > from r table 1% 0.413. Freg 266,4005 > F table 1% 7,31. Therefore, there is a very significant relations between the work organization climate and employee discipline.